Institucionalização dos Sistemas Partidários na África Lusófona – O caso cabo-verdiano - Edalina Sanches (Cadernos de Estudos Africanos, 2010)
In the study of Latin American countries Mainwaring (1998) provided a model to measure the level of party system institutionalization and explored the impact of different degrees of institutionalization on democratic consolidation. In the first part of this article, we measure the levels of party system institutionalization in the Lusophone African countries drawing on three dimensions proposed by Mainwaring – regularity of party competition, parties’ roots in society and the legitimacy of elections. In the second part we focus on Cape Verde, exploring the causes of its two-party system. Parties’ role and agency, electoral system type, and party identification are advanced as potential explanations for the bipolar nature of the party system.